Pengaruh Komunikasi dan Etos Kerja Terhadap Efektivitas Kerja Pegawai pada Kantor Camat Woha Kabupaten Bima - Aditia Rahmat Gifaris; Firmansyah Kusumayadi; Sugeng Widakdo (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to determine whether communication and work ethic have a significant effect on employee work effectiveness at the Woha District Office, Bima Regency. The research instrument used was a questionnaire with a Likert scale. The population of this study consisted of all employees of the Woha District Office, Bima Regency, totaling 85 employees, comprising 21 Civil Servants (PNS), 6 Government Employees with Work Agreements (PPPK), and 58 Part-Time PPPK employees. The sample consisted of 85 State Civil Apparatus (ASN), including both PNS and PPPK employees, using the total sampling (saturated sampling) technique. Data were collected through observation, questionnaires, and literature study. The data were analyzed using validity tests, reliability tests, multiple linear regression analysis, classical assumption tests, correlation coefficient analysis, coefficient of determination analysis, t-test, and F-test with the assistance of SPSS version 26 for Windows. The results indicate that communication has a significant effect on employee work effectiveness, work ethic has a significant effect on employee work effectiveness, and communication and work ethic simultaneously have a significant effect on employee work effectiveness at the Woha District Office, Bima Regency.